Innovations in Higher Education Curriculum: A Case Study of Interdisciplinary Programs to Foster Creativity - Hary Murcahyanto; Nofirman Nofirman; Firda Weri; Bernardus Agus Rukiyanto; Napat Chai (Yayasan Adra Karima Hubbi, 2025)
The evolving demands of the 21st century have compelled higher education institutions to redesign curricula that transcend disciplinary boundaries and cultivate creativity as a core graduate competency. Traditional mono-disciplinary programs often fail to equip students with the integrative thinking necessary for addressing complex, real-world problems. This study investigates curriculum innovations through interdisciplinary programs aimed at fostering creativity in higher education. The research seeks to identify how cross-disciplinary learning structures, collaborative projects, and flexible pedagogical designs contribute to the development of creative and adaptive learners. A qualitative case study approach was employed, involving document analysis, semi-structured interviews with faculty and students, and observation of interdisciplinary coursework across three universities. Findings reveal that interdisciplinary programs significantly enhance creative capacity by encouraging cognitive flexibility, collaborative problem-solving, and synthesis of diverse perspectives. Students reported heightened engagement and intrinsic motivation when exposed to integrated learning environments that connected theory and practice. The study concludes that curriculum innovation through interdisciplinary design is a powerful strategy for embedding creativity into higher education, though successful implementation requires institutional support, teacher training, and assessment reform aligned with creative learning outcomes.